1997
DOI: 10.1002/(sici)1097-0142(19970415)79:8<1465::aid-cncr4>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland tumors among atomic bomb survivors, 1950-1987

Abstract: These findings, supported by population-based analyses in a companion study reported elsewhere, suggest a causal role for ionizing radiation in salivary gland tumorigenesis, particularly for mucoepidermoid carcinoma, and in the induction of one type of benign tumor (Warthin's tumor).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…The association between radiation and development of mucoepidermoid carcinoma has already been established. It was initially suspected by Rice et al [23], who reported 23 mucoepidermoid carcinomas in the salivary glands after radiation exposure, and the incidence was also found to be high in survivors of the atomic bomb [24]. Since then there have been several case series of mucoepidermoid carcinoma arising after radiation exposure including eight by Modan et al [25], nine by Stites et al [26] after irradiation for childhood cancer, and nine by Beal et al [27] of which two patients had received RT for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…The association between radiation and development of mucoepidermoid carcinoma has already been established. It was initially suspected by Rice et al [23], who reported 23 mucoepidermoid carcinomas in the salivary glands after radiation exposure, and the incidence was also found to be high in survivors of the atomic bomb [24]. Since then there have been several case series of mucoepidermoid carcinoma arising after radiation exposure including eight by Modan et al [25], nine by Stites et al [26] after irradiation for childhood cancer, and nine by Beal et al [27] of which two patients had received RT for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that exposure to ionizing irradiation [10] or Epstein Barr virus (EBV) infection [11] could be risk factors. Radiation was suspected based on the observation of high incidence rates among atomic bomb survivors in Japan [12] and patients who received radiation in childhood for indications like Hodgkin lymphoma [10,13]. The current knowledge suggests that only lymphoepithelial carcinoma, constituting 0.4% of all malignant salivary gland tumors, might be strongly associated with EBV [11].…”
mentioning
confidence: 99%
“…Ionizing radiation, not ultraviolet B, is the best-known factor related to tumorigenesis [9][10][11][12]. Studies of tobacco smoking and heavy alcohol ingestion suggest higher association with salivary tumors, but these studies have conflicting results [4,13,14].…”
Section: Treatmentmentioning
confidence: 95%